Effect of sodium caseinate and vitamin A complexation on bioaccessibility and bioavailability of vitamin A in Caco-2 cells. (July 2019) - Rana, Seema; Arora, Sumit; Gupta, Chitra; Kapila, Suman
Abstract: Native sodium caseinate-vitamin A (VA) complexes (Sodium caseinate-VA complex, NaCaS-VA) and modified sodium caseinate-VA complexes i.e. Succinylated sodium caseinate-VA complex (SNaCaS-VA), reassembled sodium caseinate-VA complex (RNaCaS-VA) and reassembled succinylated sodium caseinate-VA complex (RSNaCaS-VA) were prepared and evaluated for their in-vitro bioaccessibility and in-vitro bioavailability of VA through Caco-2 cell lines.VA degraded under acidic conditions as the physiological pH during digestion in stomach was highly acidic (1.2–1.8). During in-vitro gastric digestion, sodium caseinate provided protection to VA, hence, higher VA content was retained in digesta as compared to free VA (oily form). Vitamin uptake by Caco-2 cells was significantly different for digested sodium caseinate-VA complexes as compared to free VA. The peptide content of casein and various sodium caseinate-VA complexes was monitored throughout digestion process. Variation in the complex composition had an effect on protein digestibility and peptide distribution. The bioavailability of VA through sodium caseinate-VA complexes was evaluated by exposing Caco-2 cells to the digesta of milk fortified with various complexes. The total uptake of VA by Caco-2 cells was highest for milk fortified with RSNaCaS-VA followed by RNaCaS-VA, control milk, SNaCaS-VA, NaCaS-VA and free VA. During the formation of RNaCaS-VA and RSNaCaS-VA complexes more hydrophobic sites are exposed, leading to the attachment of VA on the interior hydrophobic regions of sodium caseinate molecule. This led to higher stability of VA during gastrointestinal digestion and further resulted in higher bioaccessibility and bioavailability of vitamin A in Caco-2 cells. Graphical abstract: Unlabelled Image Highlights: In casein-VA complex, casein provided protection to VA during in-vitro gastric digestion. Higher peptide content was observed during digestion of sodium caseinate-VA complexes as compared to respective proteins. Vitamin uptake by Caco-2 cells was significantly higher for digested milk protein VA complex as compared to free vitamin A. Total uptake of vitamin A by Caco-2 cells was highest for milk fortified with reassembled succinylated casein-VA complex.